2014
DOI: 10.1261/rna.047266.114
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding by the tandem glycine riboswitch depends on aptamer dimerization but not double ligand occupancy

Abstract: The glycine riboswitch predominantly exists as a tandem structure, with two adjacent, homologous ligand-binding domains (aptamers), followed by a single expression platform. The recent identification of a leader helix, the inclusion of which eliminates cooperativity between the aptamers, has reopened the debate over the purpose of the tandem structure of the glycine riboswitch. An equilibrium dialysis-based assay was combined with binding-site mutations to monitor glycine binding in each ligand-binding site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 40 publications
8
66
2
Order By: Relevance
“…S5). This result is consistent with the findings of a previous study that analyzed the U69A mutation and found the resulting construct to be inactive for glycine binding (46). The lack of observed binding by D,G,A variants, in combination with our bioinformatic analysis, indicates that these RNAs have likely undergone a ligand specificity switch.…”
Section: Evidence For Additional Ligand Changes From Parent Guaninesupporting
confidence: 92%
“…S5). This result is consistent with the findings of a previous study that analyzed the U69A mutation and found the resulting construct to be inactive for glycine binding (46). The lack of observed binding by D,G,A variants, in combination with our bioinformatic analysis, indicates that these RNAs have likely undergone a ligand specificity switch.…”
Section: Evidence For Additional Ligand Changes From Parent Guaninesupporting
confidence: 92%
“…SAXS experiments indicated that the K-turn-containing riboswitch is more compact than the K-turn-lacking riboswitch even in the absence of glycine, consistent with partial folding of the riboswitch [65]. Recently, mutational analysis of each glycine-binding site has suggested that, although independent and not cooperative, the two ligand sites communicate via pseudo-quaternary contacts α, β, and γ [56] (Fig. 4).…”
Section: Functional Consequences Of Rna Quaternary and Pseudo-quaternmentioning
confidence: 88%
“…4C). Despite the relatively modest conservation at these sites, they covary to preserve pairing [38], and disruption of pairing greatly affects riboswitch dimerization [56]. …”
Section: Riboswitches: Pseudosymmetry In the Structure Of Ligand-bindmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Both aptamers can bind one molecule of glycine in the bulge of helix P3 6 . Cooperative glycine binding leads to dimerization of both aptamers, in which stem P1 of the first aptamer provides the scaffold for the dimer interface.…”
Section: Tandem Arrangement Of Natural Riboswitchesmentioning
confidence: 99%